Behavior of Steel plate Shear Walls consisting of reinforced concrete frame with infill low yield point (LYP) steel plate - تريكيه الزهراء; بسام حويجة; غاندي لوحو (Latakia University Journal -Engineering Sciences Series, 2023)
Frame structures systems contribute to resist the seismic loads. And there are many techniques used to improve the resistance to lateral loads where steel shear walls,which is embedded within the Frame span, are considered to be one of these ways. The steel infilled plate can be made of low yield stress steel (LYP ), This allows an early plasticization of the filling plate ,and lateness shear buckling , and The demand for concrete peripheral elements (beams , columns) may be mitigated. The research presented in this paper addresses the behavior of steel plate shear walls composed of a reinforced concrete frame and a infilled plateof low yield stress steel LYP . To achieve this purpose, A three-dimensional 3D numerical model was created using the finished elements program ABAQUS. This numerical model takes into account both geometric and physical nonlinearity.The completed numerical model is documented in comparison with experimental results drawn from published research. The documented numerical model was used to perform a parametric study to investigate the influence of certain parameters on the behavior of this structural system. These parameters mainly included the thinness of the infilled plate and the addition of horizontal and vertical supports. The results of this research confirmed that the use of a plate with a low yield stress Steel contributed to of lateness shear buckling and And making the plate plasticize by shearing is the controller of its behavior , For a thinness of no more than 150, buckling occurs very late at a relative displacement of more than 2%.